Effectiveness of partially hydrolyzed rice glutelin as a food emulsifier: Comparison to whey protein. (15th December 2016) - Xu, Xingfeng; Zhong, Junzhen; Chen, Jun; Liu, Chengmei; Luo, Liping; Luo, Shunjing; Wu, Lixin; McClements, David Julian
Highlights: H-RG has potential as a food emulsifier for certain applications. O/W emulsions containing small droplets (d < 200 nm) could be produced. H-RG had a higher surface load than whey protein isolate (WPI). H-RG emulsions were stable at relatively high pH, low salt, and low temperature. H-RG emulsions were less stable than WPI emulsions to environmental stresses. Abstract: The emulsifying properties of partially hydrolyzed rice glutelin (H-RG, 2% degree of hydrolysis) were compared to those of whey isolate protein (WPI), a commonly used protein-based emulsifier. The surface load of WPI (1% emulsifier, d32  = 167.5 nm) was 2.8 times lower than that of H-RG (3% emulsifier, d32  = 159.0 nm). Emulsions containing WPI-coated lipid droplets had better stability to pH changes (2–8), NaCl addition (0–500 mM) and thermal processing (30–90 °C, 0 or 200 mM NaCl). Nevertheless, H-RG emulsions were stable over a range of conditions: pH 6–8; NaCl ≤ 200 (pH 7); temperatures ≤ 90 °C in the absence of salt (pH 7); and temperatures ≤ 50 °C in the presence of 200 mM NaCl (pH 7). This study indicates that H-RG may be utilized as a natural emulsifier in the development of label-friendly emulsion-based food products, but that further work is needed to increase the range of applications.